Identify Changes In Conditions, Coping And Knowledge Into Dealing With Menstruation for Adolescents - Kurniawati, Rita Sri; Hanum, Latifah (Universitas Islam Jember, 2023)
Burns are a condition of damage or loss of tissue in the body caused by fire touching the body, hot water, contact with hot objects, chemicals, and sunburn. There are many incidents where emergency patients experience serious illness or even die due to errors or ignorance in providing first aid. Knowledge about treating burns is an important factor that can influence a person's knowledge, attitudes and behavior. Knowledge is the provision of health education with a pocket book. The aim of this research is to analyze the effect of health education using pocket books on increasing knowledge of burn wound management among health cadres. This research uses an experimental research design using a Pre-Test-Post Test one group with control design. With a sample size of 40 respondents using purposive sampling technique. The results of the Wilcoxon test for the treatment group using a pocket book showed a P value of 0.001, which means there was a significant difference between before and after health education with a pocket book. The results of the Mann-Whitney test obtained a P value of 0.001, which means there is a significant difference between the level of knowledge of health education using pocket books and the level of knowledge of health education using the lecture method.